2010
DOI: 10.1021/nn101840a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrode Orientations on Charge Transport in Alkanedithiol Single-Molecule Junctions

Abstract: Using first-principles calculations based on the density functional theory and the nonequilibrium Green's functions approach, we study the charge transport in Au-alkanedithiol-Au single-molecule junctions with different electrode orientations and molecular lengths. We attribute the recently measured high-/low-conductance in these heterostructures to two distinct electrode orientations, [100] and [111], which can control the electrode-molecule coupling as well as the tunneling strength by way of diverse band st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…Several studies exist in which, for a particular method, the effects of various modeling choices (e.g., system size, basis-set, exchangecorrelation potential, or number of k-vectors) on the accuracy have been investigated. 23,[28][29][30][31][32][33] The present study, however, focuses mainly on comparing different methods on the same system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies exist in which, for a particular method, the effects of various modeling choices (e.g., system size, basis-set, exchangecorrelation potential, or number of k-vectors) on the accuracy have been investigated. 23,[28][29][30][31][32][33] The present study, however, focuses mainly on comparing different methods on the same system.…”
Section: Introductionmentioning
confidence: 99%
“…Long nanowires with lengths from 200 nm to 1 µm [46] can be implemented with 1,1,0 electrodes and exhibit quantised conductance. For electrodes with other orientations, such as 1,0,1 and 1,1,1 , only short wires of length 50 to 200 nm [46] can be formed [7].…”
Section: Resultsmentioning
confidence: 99%
“…Different electrode orientations having varied band structures can affect the junction conductance and thus result in variable charge flow on the device incident from electrodes. They concluded that molecular junction having Au 1,0,0 orientation provided high conductance, while gold electrodes with 1,1,1 orientation exhibited low conductance in alkanedithiol molecular junctions [7]. In this paper, we extended their work to explore this anisotropic property of electrodes on the electrical conduction through aromatic molecular junction comprising anthracene molecule, a tricyclic alternant hydrocarbon molecule stringed between three different orientations of gold via sulphur linker atoms.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Essentially, within the DFT-NEGF scheme, the device Hamiltonian and the electronic structure are determined by DFT while the nonequilibrium quantum statistics of the device physics is determined by NEGF [8,9].…”
Section: Methodsmentioning
confidence: 99%